2018
DOI: 10.12691/ajnr-6-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Relationship between Organizational Climate and Nurses' Performance: A University Hospital Case

Abstract: Background: Competent nurses' performance and typical work climate are targets that challenge hospital administrators to achieve likely results for success. A positive work climate leads to and sustains nurses' motivation and high performance. Aim: This study aimed to explore the relationship between organizational climate and nurses' performance. Material and methods: A quantitative descriptive correlational research design was utilized. A sample of 110 nurses was recruited from all inpatients' department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This is consistent with the results of Rafaat research who claimed that there is a significant relationship between performance level and nursing competence. In this way, nurses with higher education compared to nurses with lower education, generally have a higher level of performance (26). In addition, the positive relationship between age and performance was consistent with the findings of Serra who demonstrated that there is a positive statistical relationship between nurses' age and their performance (34).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with the results of Rafaat research who claimed that there is a significant relationship between performance level and nursing competence. In this way, nurses with higher education compared to nurses with lower education, generally have a higher level of performance (26). In addition, the positive relationship between age and performance was consistent with the findings of Serra who demonstrated that there is a positive statistical relationship between nurses' age and their performance (34).…”
Section: Discussionsupporting
confidence: 87%
“…Wilmer et al, on the other hand, found that an unhealthy climate was detrimental to nurses' performance in providing quality services to patients (41). Finally, Meyer and Allen (42); and Naki and Agharsaidin (26) ensured that the favorable organizational conditions that support employees and provide good working conditions for them lead to job satisfaction and as a result can lead to a top level of performance and consequently can have a high level of performance.…”
Section: Discussionmentioning
confidence: 99%
“…A safe climate for nurses diminished burnout and allows them to have optimal professional performance and do their best to provide high quality care for patients. Abdullah Mohammad et al (2018) revealed that the positive understanding of the climate by nurses makes them more e cient [1]. Therefore, nurses should be aware of their behaviors and the effects that their behaviors may have on others in the working environment.…”
Section: Discussionmentioning
confidence: 99%
“…In today's competitive condition, the importance of human resources in the development of organizations, including health care organizations, is quite evident. Nurses are the largest workforce in healthcare organization around the world [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation